Analisis Pengendalian Kualitas Produk FIBC dengan Metode Fault Tree Analysis dan Failure Mode and Effect Analysis di PT. ABC - Billy Septian Fernando; Hidayat Hidayat; Yanuar Pandu Negoro (Universitas Islam Raden Rahmat, Malang, 2024)
PT. ABC is a plastic woven packaging company for various FIBC (Flexible Intermediate Bulk Container) line products which often experience rejection from FIBC products. The objective of the research is to recognize the categories and elements influencing the most significant defects in FIBC products at PT. ABC. The research methodology employs Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA). The FTA analysis is influenced by 3 factors, namely the man factor because the operator works under pressure, the machine factor because the spool and needle parts are not connected, and the material factor because the tying tape is damaged so that the woven fibers are not neat, so that the FMEA analysis results for stitching defects have an RPN (Risk) value. The largest Priority Number) is the part working under pressure with a score of 216. PT. ABC requires training for new employees in the QC (Quality Control) section and maintenance employees in order to reduce the risk of causing defects in FIBC (Flexible Intermediate Bulk Container) products.